Pengaruh Pengaruh Gender, Religiositas, dan Kecerdasan Intelektual Mahasiswa terhadap Perlilaku Etis Akuntan Masa Depan - Arianto Arianto; Rahman Sastrawan; Nia Pratiwi (Jurusan Akuntansi Politeknik Negeri Pontianak, 2020)
Abstract This research aims to analyze the influence of gender, religiosity, and intellectual intelligence on ethical behavior in the future. These influences will be able to cause the progress of an accounting profession whether to be good or even vice versa to be bad. The research methodology used in this study is a method with a level of clarity (explanatory) and the type of research is quantitative by conducting surveys and distributing questionnaires to respondents namely accounting students as future accountants. After the respondent fills in the questionnaire, the data will be processed presented in the form of a Likert scale. The results of this study indicate that future accountants can be trusted if they have a good ethical attitude. This research is useful to serve as a presentation of teaching materials for business and professional ethics courses.